Perkembangan yang Pesat dan Tantangan yang Dihadapi oleh Perbankan Digital di Indonesia - Muhammad Raihan Akbar (Prodi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam Universitas Islam Bunga Bangsa Cirebon, 2023)
Abstract The development of information technology and digital transformation has brought significant changes to the banking industry in Indonesia. The emergence of digital banking has opened new opportunities as well as challenges in terms of law and consumer protection. In the context of digital banking, the main challenge is consumer protection. Customers expect secure digital banking services with adequate protection for their personal data. However, the lack of clear and comprehensive regulations regarding consumer protection creates potential risks, such as data breaches. To overcome these challenges, serious efforts are needed, including the establishment of policies and regulations that protect consumers in the use of digital banking services. Cooperation between the government, regulatory bodies, and industry players is also necessary. Adequate regulations and clear provisions will ensure the sustainability and healthy growth of digital banking. Additionally, consumer trust in digital banking needs to be strengthened through policies that prioritize the protection of personal data and effective risk management. Awareness of the importance of personal data protection also needs to be increased. Overall, digital banking has become an integral part of the digital financial ecosystem in Indonesia. However, the legal challenges, especially in consumer protection, indicate the need for more comprehensive regulations and increased awareness of the importance of personal data protection. By overcoming these challenges, digital banking can continue to grow sustainably, provide innovative services, and bring broader benefits to society. Keywords: Digital Banking, Consumer Protection, Regulatory Framework, Trust and Security, Financial Ecosystem.